Autoantibodies directed against insulin receptor during the course of Castleman disease: a new case reaffirming autoimmune hypoglycemia as a relapse warning signal - Xavier Jannot; Martine Auclair; Martin Martinot; Amin Maazouzi; David Boutboul; Corinne Vigouroux; Yannick Dieudonné (European Journal of Case Reports in Internal Medicine)
This case study presents the case of a 54-year-old human immunodeficiency virus (HIV)-positive male who developed type B insulin resistance syndrome (TBIRS) in conjunction with a relapse of human herpesvirus 8 (HHV8)-positive multicentric Castleman disease (MCD). This case is only the sixth reported instance of TBIRS associated with HHV8-associated MCD. The diagnosis was confirmed by the presence of anti-insulin receptor autoantibodies, and the patient was treated effectively with rituximab, with no relapse in follow-up. The cases described are discussed, along with the differences between them and our own case. Additionally, the potential for an autoimmune complication of MCD, even when HIV is well controlled, is addressed, as well as the available therapeutic approaches.